Global Well-Posedness and Incompressible Limit of the Hall-Magnetohydrodynamic System in a Bounded Domain (Journal of Partial Differential Equations, 2024)
In this paper we firstly prove the global well-posedness for the compressible Hall-magnetohydrodynamic system in a bounded domain when the initial datais small. On this basis, we continue to study the convergence of the correspondingequations with the well-prepared initial data as the Mach number tends to zero.
Keywords: Compressible Hall-magnetohydrodynamic system; global well-posedness; incompressible limit.